Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To solve the equation [tex]\(\cos(11b + 2) = \sin(12b - 4)\)[/tex], we can use a trigonometric identity. The identity that relates cosine and sine is given by:
[tex]\[ \cos(x) = \sin(90^\circ - x) \][/tex]
Applying this identity, we can rewrite the original equation [tex]\(\cos(11b + 2)\)[/tex] as:
[tex]\[ \cos(11b + 2) = \sin(90^\circ - (11b + 2)) \][/tex]
So, the given equation [tex]\(\cos(11b + 2) = \sin(12b - 4)\)[/tex] can be rewritten using this identity as:
[tex]\[ \sin(90 - (11b + 2)) = \sin(12b - 4) \][/tex]
Simplify the argument of the sine function on the left side:
[tex]\[ \sin(90 - 11b - 2) = \sin(12b - 4) \][/tex]
[tex]\[ \sin(88 - 11b) = \sin(12b - 4) \][/tex]
For the sine of two angles to be equal, the angles themselves must either be equal, or they must sum to [tex]\(180^\circ\)[/tex] given the periodic nature of the sine function. Therefore, we have:
[tex]\[ 88 - 11b = 12b - 4 \][/tex]
or
[tex]\[ 88 - 11b = 180^\circ - (12b - 4) \][/tex]
Let’s solve the first equation:
[tex]\[ 88 - 11b = 12b - 4 \][/tex]
Move all terms involving [tex]\(b\)[/tex] to one side and constants to the other:
[tex]\[ 88 + 4 = 12b + 11b \][/tex]
[tex]\[ 92 = 23b \][/tex]
Divide both sides by 23:
[tex]\[ b = \frac{92}{23} \][/tex]
Simplify:
[tex]\[ b = 4 \][/tex]
Therefore, the value of [tex]\(b\)[/tex] is [tex]\( \boxed{4} \)[/tex].
[tex]\[ \cos(x) = \sin(90^\circ - x) \][/tex]
Applying this identity, we can rewrite the original equation [tex]\(\cos(11b + 2)\)[/tex] as:
[tex]\[ \cos(11b + 2) = \sin(90^\circ - (11b + 2)) \][/tex]
So, the given equation [tex]\(\cos(11b + 2) = \sin(12b - 4)\)[/tex] can be rewritten using this identity as:
[tex]\[ \sin(90 - (11b + 2)) = \sin(12b - 4) \][/tex]
Simplify the argument of the sine function on the left side:
[tex]\[ \sin(90 - 11b - 2) = \sin(12b - 4) \][/tex]
[tex]\[ \sin(88 - 11b) = \sin(12b - 4) \][/tex]
For the sine of two angles to be equal, the angles themselves must either be equal, or they must sum to [tex]\(180^\circ\)[/tex] given the periodic nature of the sine function. Therefore, we have:
[tex]\[ 88 - 11b = 12b - 4 \][/tex]
or
[tex]\[ 88 - 11b = 180^\circ - (12b - 4) \][/tex]
Let’s solve the first equation:
[tex]\[ 88 - 11b = 12b - 4 \][/tex]
Move all terms involving [tex]\(b\)[/tex] to one side and constants to the other:
[tex]\[ 88 + 4 = 12b + 11b \][/tex]
[tex]\[ 92 = 23b \][/tex]
Divide both sides by 23:
[tex]\[ b = \frac{92}{23} \][/tex]
Simplify:
[tex]\[ b = 4 \][/tex]
Therefore, the value of [tex]\(b\)[/tex] is [tex]\( \boxed{4} \)[/tex].
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.